2019
DOI: 10.1001/jamadermatol.2019.0039
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Risk of Mental Disorders in Denmark

Abstract: Nijsten T, Meads DM, de Korte J, et al. Cross-cultural inequivalence of dermatology-specific health-related quality of life instruments in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 6 publications
(18 reference statements)
0
36
0
Order By: Relevance
“…Thereafter, 25 studies were thought to be eligible and evaluated for full-text review. Sixteen studies were excluded, and the nine remaining studies (Abuabara et al, 2010;Feldman et al, 2015;Chen et al, 2018;Mitchell et al, 2018;Pezzolo et al, 2018;Huang et al, 2019;Leisner et al, 2019;Lin et al, 2019;Kim et al, 2020) were included. The search strategy and study selection are shown in Figure 1.…”
Section: Characteristics Of the Pooled Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thereafter, 25 studies were thought to be eligible and evaluated for full-text review. Sixteen studies were excluded, and the nine remaining studies (Abuabara et al, 2010;Feldman et al, 2015;Chen et al, 2018;Mitchell et al, 2018;Pezzolo et al, 2018;Huang et al, 2019;Leisner et al, 2019;Lin et al, 2019;Kim et al, 2020) were included. The search strategy and study selection are shown in Figure 1.…”
Section: Characteristics Of the Pooled Studiesmentioning
confidence: 99%
“…Of the nine studies, four were conducted in East Asia (Chen et al, 2018;Huang et al, 2019;Lin et al, 2019;Kim et al, 2020), three in Europe (Abuabara et al, 2010;Pezzolo et al, 2018;Leisner et al, 2019), and two in the USA (Feldman et al, 2015;Mitchell et al, 2018). Five were cohort studies (Abuabara et al, 2010;Pezzolo et al, 2018;Huang et al, 2019;Leisner et al, 2019;Kim et al, 2020); two were case-control studies (Chen et al, 2018;Lin et al, 2019); one was a cross-sectional study (Mitchell et al, 2018), and the remaining one was a retrospective study (Feldman et al, 2015). Almost all the studies used the codes of the International Statistical Classification of Diseases and Related Health Problems as a diagnostic basis.…”
Section: Characteristics Of the Pooled Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Psoriasis is a chronic, proliferative autoimmune skin disease governed by various genetic factors and stimulated by multiple environmental factors with a global prevalence of 2 − 3% [1,2]. The characteristic skin lesions in psoriasis are red papules or plaques covered with several layers of accumulated silverwhite scales that can be at a level higher than the skin surface.…”
Section: Introductionmentioning
confidence: 99%